Investissements américains directs et compétitivité technologique européenne - Dunning, John; Cantwell, John (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractThis paper examines the impact of US firms on technological competitiveness in Europe between 1955-75 through a dynamic application of the eclectic theory of international trade and production. It looks at the improvement in the trading performance of European countries, and finds that in certain larger countries and sectors that indigenous firms also improved their position. This is further found to be related to the transfer of technology from the US to Europe, and its diffusion to European firms where this has taken place.